ATENÇÃO ODONTOLÓGICA EM PACIENTES HOSPITALIZADOS E PORTADORES DE DOENÇAS INFECTOCONTAGIOSAS - de LEMES, Edson Paulo; BOHN, Joslei Carlos; CHAIBEN, Cassiano Lima; PETRONI, Vinicius Villas Boas; de LIMA, Antonio Adilson Soares (DENS, 2011)